2016
DOI: 10.1103/physreva.93.012505
|View full text |Cite
|
Sign up to set email alerts
|

TaN, a molecular system for probingP,T-violating hadron physics

Abstract: All-electron configuration interaction theory in the framework of the Dirac-Coulomb Hamiltonian has been applied to the TaN molecule, a promising candidate in the search for Beyond-Standard-Model physics in both the hadron and the lepton sector of matter. We obtain in the first excited 3 ∆1 state a P, T -odd effective electric field of 36.0 GV cm , a scalar-pseudoscalar P, T -odd interaction constant of 32.8 [kHz], and a nuclear magnetic-quadrupole moment interaction constant of 0.74 [ 10 33 Hz e cm 2 ]. The l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…for ThF + the estimate from Ref. [11] differs from that of ab-initio correlation calculation [29] by about 3 times [62] The obtained W M in HfF + is very close to the value of W M in the ThF + [29] and slightly smaller than that in TaN [63,64]. Note, however, that the HfF + cation is already under active investigation for the other T,P-odd effects and similar experimental technique can be used to search for the nuclear MQM.…”
Section: Resultsmentioning
confidence: 99%
“…for ThF + the estimate from Ref. [11] differs from that of ab-initio correlation calculation [29] by about 3 times [62] The obtained W M in HfF + is very close to the value of W M in the ThF + [29] and slightly smaller than that in TaN [63,64]. Note, however, that the HfF + cation is already under active investigation for the other T,P-odd effects and similar experimental technique can be used to search for the nuclear MQM.…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment the electron spin rotation angle in an external electric field, arising due to the existence of the electron EDM, was measured. Theoretical calculations for the ThO molecule were given in [29,30]. We should mention also a proposal to measure P, T-odd effects in the ground 3 1 state of WC molecule [31].…”
mentioning
confidence: 99%
“…Nevertheless, many studies have demonstrated that the quantum calculations should also include the relativistic spin-orbit interaction for At-containing compounds. [42,44,[48][49][50][51][52][53] For instance, the interaction energy of At-mediated XBs can be affected by SOC effects up to 35 %. [26,45,46] Hence, all these systems have been additionally investigated through twocomponent (2c) relativistic calculations.…”
Section: Two-component Relativistic Resultsmentioning
confidence: 99%
“…Indeed, astatine is to date the heaviest halogen element and the most polarisable one. [42] It is therefore appealing to probe the XB interaction in Y 3 CÀ X···Z À systems from the perspective of the most potent XB-donor element. Astatine (Z=85) is a radioelement whose second long-lived isotope, At-211, has been recently identified as being of high potential interest for nuclear medicine applications.…”
Section: Introductionmentioning
confidence: 99%